1995
DOI: 10.1159/000244164
|View full text |Cite
|
Sign up to set email alerts
|

Acute Entry of Bilirubin into Rat Brain Regions

Abstract: In kemicterus bilirubin appears at higher concentrations in the basal ganglia, the cerebellum, and the medulla. The mechnism for this distribution is unknown, but might involve differences in bilirubin entry among brain regions. We infused [3H]bilirubin (30 mg/kg over 5 min) intravenously into young Sprague-Dawley rats (n = 21, weight 144 ± 10 g, mean ± SD). Blood was sampled from the tail, and groups of rats were killed at 15, 30, 45, 60, and 75 min by intravenous pentobarbital. After in situ flush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…It is not clear whether this phenomenon is primary in the sense that it is causally related to the neu ronal dysfunction and death which occurs in kernicterus, or whether the staining phenome non is secondary and only functions as a marker of other processes. In our studies so far we have failed to find any relationship between the kinetics of bilirubin entry into or clearance from the brain and the kernicteric staining phenomenon [14][15][16][17], It has been suggested that opening of the blood-brain bar rier may be important for regional bilirubin staining, but numerical data were not avail able to back up this theory [18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is not clear whether this phenomenon is primary in the sense that it is causally related to the neu ronal dysfunction and death which occurs in kernicterus, or whether the staining phenome non is secondary and only functions as a marker of other processes. In our studies so far we have failed to find any relationship between the kinetics of bilirubin entry into or clearance from the brain and the kernicteric staining phenomenon [14][15][16][17], It has been suggested that opening of the blood-brain bar rier may be important for regional bilirubin staining, but numerical data were not avail able to back up this theory [18].…”
Section: Discussionmentioning
confidence: 96%
“…the cerebral cortex. Some studies have suggested that these differences may be related to biliru bin uptake [12,13], However, in other studies using short-term (1 h) bilirubin infusions in young rats, differences in bilirubin concentra tions between brain regions were not signifi cant [14], In recent studies of the kinetics of bilirubin entry into and clearance from rat brain regions under different conditions, no differences were found that might explain the staining pattern of kernicterus [15][16][17], Some have suggested that opening of the blood-brain barrier may contribute to localized bilirubin staining in the brain [ 18], though the power of this observation was limited by the lack of analysis of actual brain bilirubin content. In our own studies, hyperosmolar opening of the blood-brain barrier in rats has not resulted in a kernicteric staining pattern [14,17], Although the subcellular localization of bil irubin-oxidizing activity is known, and its role in the detoxification of bilirubin in the brain has been hypothesized [4,19], its distri bution between regions in the brain has not been studied.…”
mentioning
confidence: 99%
“…Also, previous studies in rats have failed to demonstrate a relationship between the kernicterus phenomenon and the kinetics of short term bilirubin entry into brain [9,21]. How ever, studies in newborn piglets have found an increased entry of bilirubin into brain regions in which blood flow was increased by hyper capnia [6], A significantly increased entry of bilirubin into medulla, but not in other sub cortical regions, was also found during control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Using the rat infusion model, we were not able to show that bilirubin distribution patterns in brain under conditions that increased the free bilirubin concentrations (drug displacement), opened the blood-brain barrier (hyperosmolality), or increased brain bloodflow (hypercapnia) corresponded to the pattern seen in kernicterus. 15 Subsequently, we attempted to separate what happens during the phase of acute entry of bilirubin into brain, 16 as well as the phase of bilirubin clearance from brain. 17 These studies also did not yield any clues to the mechanism of regional distribution seen in kernicterus.…”
Section: Entry Distribution and Disposition Of Bilirubin In Brainmentioning
confidence: 99%